Ibadah Sa’i Dengan Menggunakan Eskalator : (Penerapan Metode Ilhaq Masail bi Nadhairiha) - Ishak, Sufriadi (Institut Agama Islam Al-Aziziyah Samalanga, 2024)
This research discusses the method of finding law through ilhaq masail bi nadhairiha in the practice of sa'i worship using escalators. Of course, facilities in the form of escalators built by local authorities will have an impact on the worship not being fully carried out by each individual in its entirety, this raises legal questions about whether it is valid or not. To find legal answers, many methods are used, one of which is familiar among Islamic intellectuals is the Ilhaq Masail Bi Nadhairiha method, where this method is the first step in actualizing the book of Thurats to be able to be adaptive in answering contemporary problems. The research method used is a qualitative method with a descriptive analysis approach, with this approach we want to find a comprehensive problem analysis for the existence of a legal fatwa that is a solution with balanced library materials. The results of the research show that there is a mistake in the law on escalators without walking, some are of the opinion that it is not permissible, some are of the opinion that it is permissible in urgent conditions (dharurat) and some say it is absolutely permissible. Furthermore, the local authorities' actions in building escalators are justified provided that they still provide free space for jogging as is the basic requirement for sa'i worship.